2017
DOI: 10.3988/jcn.2017.13.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Association ofHelicobacter pyloriwith Parkinson's Disease

Abstract: Background and PurposeParkinson's disease (PD) is a major neurological disorder that requires lifelong treatment, and the combined presence of Helicobacter pylori (H. pylori) infection can increase the required anti-PD medications. We aim to investigate the effect of H. pylori infection in Indian PD patients.MethodsWe prospectively recruited 36 PD patients from December 2007 to January 2011. All patients underwent a detailed neurological evaluation and serological examination for H. pylori infection. Seroposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
(41 reference statements)
4
37
0
Order By: Relevance
“…The mean IgG titer was significantly higher among patients with PD. Previous studies have reported lower rates of HP positivity, whereas the values obtained in our study were considerably higher (5,21). We also determined higher levels of HP antibody elevation in our control group.…”
Section: Discussionsupporting
confidence: 46%
“…The mean IgG titer was significantly higher among patients with PD. Previous studies have reported lower rates of HP positivity, whereas the values obtained in our study were considerably higher (5,21). We also determined higher levels of HP antibody elevation in our control group.…”
Section: Discussionsupporting
confidence: 46%
“…Alterations in the gut microbiome are believed to contribute to many different human health problems (Bercik et al, 2011;Boulange et al, 2016;Bravo et al, 2011;Clapp et al, 2017;Clemente et al, 2012;Dinan and Cryan, 2017b;Fung et al, 2017;Kelly et al, 2017;Ochoa-Reparaz and Kasper, 2014;Parracho et al, 2005;Tognini, 2017;Walters et al, 2014;Zhang et al, 2015). Next to the direct effects H. pylori infection on the gastrointestinal system (Camilo et al, 2017;Johnson and Ottemann, 2017;Kusters et al, 2006;Li et al, 2016;Mayer et al, 2014;Pere-Vedrenne et al, 2017;Teng et al, 2017), it has been associated with the occurrence of different neurodegenerative disorders, including Alzheimer's disease (Alvarez-Arellano and Maldonado-Bernal, 2014;Doulberis et al, 2017;Roubaud Baudron et al, 2016;Wirdefeldt et al, 2011;Wong et al, 2014) and Parkinson's disease (Alvarez-Arellano and Maldonado-Bernal, 2014;Blaecher et al, 2013;Dinan and Cryan, 2017a;Mridula et al, 2017;Mulak and Bonaz, 2015;Wirdefeldt et al, 2011;Wong et al, 2014). We recently highlighted a similar association of gastric H. suis infections in Parkinson's disease (Blaecher et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In double-blind trials of biopsy-proven H. pylori eradiation [ 39 ], improved hypokinesia was independent of any (stable, long t ) anti-parkinsonian medication, and receipt of levodopa was an exclusion. Antimicrobial treatment to eliminate H. pylori infection has also been shown to improve L-dopa absorption in the gut [ 29, 30, 33, 37, 40, 41 ]. For example, Pierantozzi, et al, found that H. pylori eradicated PD patients ( n = 17) showed a significant increase in gut L-dopa absorption, in contrast with PD patients ( n = 17) given placebo, which had worsening gastritis scores and impaired L-dopa absorption [ 33 ].…”
mentioning
confidence: 99%